Impact of English on the Career of Engineering Students: A Brief Overview in G(local) Context - Shrestha, Rup Narayan; Pahari, Bharat Raj; Awasthi, Jai Raj (Journal of the Institute of Engineering, 2016)
The present article highlights the importance of the English language in the career of the students of engineering both in global and local contexts. The main objective of this article is to explore the impact of English language on the career of the students of engineering all over the world in general and in Nepal in particular. Based primarily on the literature review for the necessary data, it reveals the fact that the English language is a most essential language for the students of engineering not only in Nepal but it is equally relevant in the global context as well. It suggests that there is widespread application of English language in the feld of engineering. Journal of the Institute of Engineering, 2015, 11(1): 182-188